Magnetic and electronic phase separation driven by structural clustering in La0.7 (Ca1-y Sry)0.3MnO3 thin films - Prokhorov, V.G.; Komashko, V.A.; Kaminsky, G.G.; Lee, Y.P.; Hyun, Y.H.; Yu, K.K.; Park, J.S.; Svetchnikov, V.L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The structural, magnetic and transport properties of La0.7 (Ca1-y Sry)0.3MnO3 films deposited on LaAlO3 (001) single-crystalline substrate by rf-magnetron sputtering using «soft» (or powder) targets are investigated. It was found that at 0.3 ≤ y ≤ 0.5 both rhombohedral (R̅3c) and orthorhombic (Pnma) crystal phases are coexistent at room temperature, forming a nanoclustered microstructure. The clustered films manifest the two-stage magnetic and electronic transition, which are typical for the phase-separated systems. It was shown that for 0.5&#8805 y ≥0 the nonlinear (almost parabolic) field-dependent magnetoresistance is typical at room temperature while for 0.65≤ y ≤1.0 its transform to the linear behavior. The magnetotransport properties of the films are explained within the framework of a field-dependent activation energy model. The magnetic phase diagram for the La0.7 (Ca1-y Sry)0.3MnO3 thin-film system is presented.